Association between composite dietary antioxidant index and increased urinary albumin excretion: a population-based study - Li, Shaopeng; Yang, Suqiong; Wang, Yong; Lin, Zongqi; Chen, Fuyuan; Gao, Qinghe; Cai, Jiantong (Frontiers in Nutrition, 2025)
IntroductionThe Albumin-Creatinine Ratio (ACR) is a key biomarker for early kidney disease detection and is predictive of chronic kidney disease (CKD) progression and associated cardiovascular risks. Antioxidant diets, indicated by the Composite Dietary Antioxidant Index (CDAI), may reduce oxidative stress and alter albumin urinary excretion rates. This study explores the relationship between CDAI and albuminuria.Materials and methodsData on intake of vitamins A, C, E, zinc, selenium, and beta-carotene from the NHANES database (2007–2018) were used to compute CDAI scores. To measure urinary albumin, the ACR levels were assessed. The association between CDAI and ACR was analyzed through multivariate logistic regression, subgroup analysis, and interaction tests, incorporating a generalized additive model (GAM) to evaluate potential non-linear relationships.ResultsA total of 28,601 participants were included with an average CDAI of 0.302 ± 3.895. Those in higher CDAI quartiles showed a reduced likelihood of elevated ACR. The prevalence of increased ACR decreased across the CDAI quartiles from 13.89% in Q1 to 10.11% in Q4. Higher CDAI scores were inversely related to ACR (OR: 0.99, 95% CI: 0.97–1.00), with a significant interaction effect by BMI (p = 0.0048). In males, a distinct L-shaped relationship was noted, with a negative correlation between CDAI and ACR to the left of the inflection point at 0.53 (OR: 0.95, 95% CI: 0.91–0.98).ConclusionIncreasing CDAI is associated with lower ACR and reduced risk of albuminuria, suggesting that dietary antioxidants may benefit renal and cardiovascular health.